Kinetics and thermodynamics of Cd(II) adsorption onto pyrite and synthetic iron sulphide - Erdem, Mehmet; Ozverdi, Arzu (Elsevier Science Bv, 2006)
In this paper, the Cd(II) adsorption abilities of pyrite and synthetic iron sulphide (SIS) were studied. Experiments were carried out as a function of pH, Cd(II) concentration, contact time and temperature. Maximum adsorption yields for pyrite and SIS were determined to be 34.2% and 65.8% under the conditions of initial Cd(II) concentration of 100 mg/l, pH 5.4, contact time of 120 min and adsorbent dosage of 20 g/l, respectively. The adsorption data fitted both the Langmuir and Freundlich adsorption models. Adsorption capacities of SIS and pyrite at 25 degrees C were found to be 3.05 and 2.08 mg Cd(II)/g, respectively. The first-order and pseudo second-order rate expressions were applied to experimental data and it was determined that the adsorption process followed the first-order kinetic model. In addition, activation energy values and some thermodynamic parameters such as Delta G degrees, Delta H degrees and Delta S degrees for the cadmium adsorption processes were calculated from the isotherm and kinetic data. The adsorption of Cd(II) on to SIS and pyrite was found to be endothermic and spontaneous. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cadmium; adsorption; kinetics; isotherms; pyrite; iron sulphide